2002
DOI: 10.1159/000065457
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of Rosmarinic Acid on Mesangioproliferative Glomerulonephritis in Rats

Abstract: Background: Rosmarinic acid is known to be a natural phenolic compound widely distributed in Labiatae herbs such as rosemary, sweet basil, and perilla. In the present study, we evaluated the suppressive effects of rosmarinic acid on mesangioproliferative glomerulonephritis in vivo, which was induced by intravenous injection of rabbit anti-rat thymocyte serum (ATS) to rats. Methods: Rosmarinic acid was orally administered to the rats at a dose of 100 mg/kg/day from the day of ATS injection (day 0) to day 8 when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 15 publications
1
30
0
1
Order By: Relevance
“…16) This result was later confirmed by in vivo experiments, using the experimental model of ATS-induced glomerulonephritis in rats. 17) Again, as in other cases, the dimer of caffeic acid showed a much more pronounced effect than monomeric caffeic acid. Hence, it is not surprising that a tetramer of caffeic acid, lithospermic acid B, has a strong protective effect on rats with induced diabetic nephropathy.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…16) This result was later confirmed by in vivo experiments, using the experimental model of ATS-induced glomerulonephritis in rats. 17) Again, as in other cases, the dimer of caffeic acid showed a much more pronounced effect than monomeric caffeic acid. Hence, it is not surprising that a tetramer of caffeic acid, lithospermic acid B, has a strong protective effect on rats with induced diabetic nephropathy.…”
mentioning
confidence: 52%
“…19) The content of rabdosiin was 3.4% dry wt in root cultures, representing the highest yield reported for biotechnological or natural rabdosiin sources, 20) but E. sericeum callus cultures synthesized much smaller quantities of CAMs than E. sericeum root cultures, 17) which restricted their practical usage. Since callus (suspension) cultures have several practical advantages over root cultures (besides hairy roots), it is of considerable interest to obtain a high-producing E. sericeum callus culture.…”
mentioning
confidence: 99%
“…Rosmarinic acid is a phenolic compound widely distributed in various plants such as Ocimum basilicum, Melissa officinalis, Rosmarinus officinalis, Mentha spicata, e Perilla frutescen e C. verbenacea (Makino et al, 2002;Ticli et al, 2005), commonly found in species from Boraginaceae family. In addition, this compound is the phytochemical marker to C. verbenaceae due its properties and abundance in this species.…”
Section: Introductionmentioning
confidence: 99%
“…About pharmacological activity, rosmarinic acid is reported exhibiting anti-inflammatory effects, including inhibition of C 3-convertase, C 5 -convertase, 5-lipoxygenase, histamine release from mast cells, phospholipase A 2 and sequesters reactive oxygen species (Makino et al, 2002;Ticli et al, 2005;dos Santos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have fibrinolytic and antioxidative activity (Ramírez et al, 2004;Nusier et al, 2007). Accumulating evidence suggests that the protective effects of RO against oxidative damage could be attributed to its anti-oxidative properties (Makino et al, 2002;Tseng et al, 1997). The anti-oxidant activity of RO could be attributed to its phenolic contents, namely protocatechuic acid (Wang et al, 2000) and anthocyanins Tsai & Huang, 2004).…”
Section: Introductionmentioning
confidence: 99%